2022
DOI: 10.1039/d2se00450j
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photostability of CsPbI2Br-based perovskite solar cells through suppression of phase segregation using a zwitterionic additive

Abstract: Photoinduced aging of a widely used perovskite light absorber such as CsPbI2Br can be suppressed significantly by using d,l-asparagine as a stabilizing agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…The enhanced photostability of the device was attributed to the stabilization of the perovskite phase by 4,2-CBA and the reduction of the photodegradation rate. [38] It can also be observed in UV-vis spectra (Figure 5d) that the absorptance decreased more significantly for the pristine perovskite film than that of the 4,2-CBA incorporated film, which was consistent with the results of the aging experiments shown in Figure 5c.…”
Section: Resultssupporting
confidence: 87%
“…The enhanced photostability of the device was attributed to the stabilization of the perovskite phase by 4,2-CBA and the reduction of the photodegradation rate. [38] It can also be observed in UV-vis spectra (Figure 5d) that the absorptance decreased more significantly for the pristine perovskite film than that of the 4,2-CBA incorporated film, which was consistent with the results of the aging experiments shown in Figure 5c.…”
Section: Resultssupporting
confidence: 87%
“…The presence of iodine-rich or bromine-rich regions due to photoinduced phase segregation dramatically affects the absorption and emission properties of WB perovskites. 65,72,73 Although the time of phase segregation is very short, the experimental results showed that the process was time dependent, and exhibits significant changes in absorption and emission behavior 22 Fig. 3(a) shows the variation of photoinduced phase segregation with time, and an emission peak appeared at B550 nm (B2.25 eV) and slowly redshifts to B710 nm (B1.75 eV) over the first 60 s under a pulsed laser with a low excitation intensity (10 W cm À2 ), which greatly affected the light absorption of WB perovskites.…”
Section: Wb Perovskite Device Performance Under Operation Conditionsmentioning
confidence: 99%
“…It should be noted that the cubic phase of CsPbI 3 , while experimentally unstable at room temperature in its bulk phase [ 31 ], may be stabilized in quantum dots [ 32 ] and also serves as a good reference point for comparison for CsPbI 2 Br as well as a relatively simple and robust model since we do not have to consider the orientation of the organic cation, which can greatly change the calculated defect formation energies in perovskite materials [ 33 , 34 ]. CsPbI 2 Br has been noted for its superior thermodynamic stability [ 35 ] and is also somewhat closer to the ideal Goldschmidt tolerance when compared to CsPbI 3 [ 29 ] because of improved phase stability. For photovoltaic applications, α-CsPbI 2 Br and β-CsPbI 2 Br are prospective and recent experimental work has demonstrated the possibility of stabilizing α-CsPbI 2 Br via dilute FeCl 2 incorporation [ 36 ].…”
Section: Introductionmentioning
confidence: 99%